The Artificial Intelligence Conference, San Francisco 2018. (O'Reilly Media, 2018)
"The Artificial Intelligence Conference SF 2018 was all about putting AI to work right now, giving conference attendees the opportunity to cut through the noise to see what's real and what's coming soon in the world of applied AI. Want to hear what Andrew Feldman (Cerebras Systems) can share about the next generation of machine learning hardware? What Ting-Fang Yen (DataVisor) reveals about the ways her company creates real-time, scalable fraud detection solutions using deep learning, Spark and TensorFlow? What Sarah Bird (Facebook) can teach us about the Amazon-Microsoft-Facebook backed Open Neural Network Exchange (ONNX) and why this framework makes it possible to rapidly move AI projects from research to reality? This video compilation gives you the chance to learn about these subjects and much, much more. It's a complete video recording of the 15 keynotes, 11 tutorials, and 100+ technical sessions delivered at AI SF 2018 by the world's top AI strategists, developers, researchers, and data scientists."--Resource description page